Land management and factors influencing agroforestry adoption on potato farmlands in the Dieng Plateau, Indonesia - ARI PUJIWINARKO; TRI RETNANINGSIH SOEPROBOWATI; KISMARTINI KISMARTINI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Pujiwinarko A, Soeprobowati TR, Kismartini. 2024. Land management and factors influencing agroforestry adoption on potato farmlands in the Dieng Plateau, Indonesia. Biodiversitas 25: 2623-2641. The Dieng area in Indonesia has long experienced agricultural land degradation, and intensive potato monoculture farming is one of the leading causes. Vegetative-based programs such as agroforestry have been implemented, but the level of adoption still needs to improve. This research aims to evaluate land management systems and analyze practices and the factors influencing agroforestry adoption of potato farming land in Dieng. We surveyed 260 potato farmers and interviewed 12 Key Informant Interviews (KII). Data were analyzed using binary logistic regression, descriptive statistics, and narrative approaches. Our research found changes in how potato farmers manage land regarding planting frequency and mulch use. The combination of potatoes and MPTS (Multi-Purpose Tree Species) is the plant composition most commonly found in agroforestry practices. Carrots (Daucus carota L.) are the vegetables that farmers most often plant when rotating potato crops. Mountain pine (Casuarina junghuhniana Miq.) and Carica (Carica pubescens (A.DC.) Lenne & K.Koch) are the species of trees and MPTS most commonly found in the fields of potato farmers who adopt agroforestry. Farmers maintain MPTS and trees on their land due to their suitability with main food crops and economic considerations. Several factors, including the species of energy source, use of mulch, frequency of potato planting, perception of disasters, farmer interest, prices, markets, the experience of vegetative activities, and government policy, significantly influence agroforestry adoption. Considering local agricultural systems, including the presence of principal crops and their management on the land, socio-economic and farmers' perspectives are essential to further increase agroforestry adoption in Dieng.